Bio-Derived Hierarchical 3D Architecture from Seeds for Supercapacitor Application - Pratthana Intawin (2018)
© 2017, The Minerals, Metals & Materials Society. The generation and storage of green energy (energy from abundant and nonfossil) is important for a sustainable and clean future. The electrode material in a supercapacitor is a major component. The properties of these materials depend on its inherent architecture and composition. Here, we have chosen sunflower seeds and pumpkin seeds with a completely different structure to obtain a carbonaceous product. The product obtained from sunflower seed carbon is a three-dimensional hierarchical macroporous carbon (SSC) composed of many granular nanocrystals of potassium magnesium phosphate dispersed in a matrix. Contrary to this, carbon from pumpkin seeds (PSC) is revealed to be a more rigid structure, with no porous or ordered morphology. The electrochemical supercapacitive behavior was assessed by cyclic voltammetry and galvanostatic charge–discharge tests. Electrochemical measurements showed that the SSC shows a high specific capacitance of 24.9 Fg−1as compared with that obtained (2.46 Fg−1) for PSC with a cycling efficiency of 87% and 89%, respectively. On high-temperature cycling for 500 charge–discharge cycles at 0.1 Ag−1, an improved cycling efficiency of 100% and 98% for SSC and PSC, respectively, is observed.